Solidarity's secret : the women who defeated Communism in Poland - Penn, Shana (Univ. of Michigan Press, 2005)
Introduction : national secret -- Women at the gates : Anna Walentynowicz and the August 1980 strikes -- Solidarity's "blank spot" : the legal period and martial law -- Dark circles : building the Solidarity underground -- Floating offices : publishing the underground newspaper -- Wild card: the female stereotype as camouflage -- A third space : mutual dependencies and cooperation -- Patient revolution : women and leadership -- "Our romantic model" : myth, literature, and women's place -- In the end, the beginning : adjustments and new problems for women after 1989 -- Filling in the "blank spot" : the public discourse on women